The Association between the Epicardial Adipose Tissue Thickness and Oxidative Stress Parameters in Isolated Metabolic Syndrome Patients: A Multimarker Approach - Bulent Demir; Esra Demir; Gonul Acıksarı; Turgut Uygun; Irem Kırac Utku; Asuman Gedikbasi; Ilker Murat Caglar; Osman Pirhan; Hande Oktay Tureli; Ersan Oflar; İsmail Ungan; Serkan Ciftci; et al. (International Journal of Endocrinology)
The risk for cardiovascular diseases and type 2 diabetes mellitus significantly increases in the patient population with metabolic syndrome (MeS). The present study aimed to investigate the association between the epicardial adipose tissue thickness (EATT) and the oxidative stress parameters in MeS patients. The study included 181 patients as a patient group of 92 consecutive patients with MeS and a control group of 89 consecutive patients with similar age and gender. EATT was evaluated by transthoracic echocardiography. Serum levels of total oxidant status (TOS), total antioxidative capacity (TAS), paraoxonase-1 (PON-1), and arylesterase activities were measured. EATT was higher in the MeS group compared to the control group (6.0 ± 2.0 mm and 4.0 ± 1.0 mm, resp.; P<0.001). The level of TOS was higher in the MeS group compared to the control group (P<0.001). Additionally, the TAS level was higher in the MeS group compared to the control group (P<0.001). Furthermore, the serum levels of PON-1 and arylesterase were lower in the MeS group compared to the control group (P<0.001). EAT may cause an increased risk of cardiovascular diseases by leading to increased oxidative stress in patients with MeS.